#TITLE_ALTERNATIVE# - NOVRIAL (NIM 15107057); Pembimbing: Dr.rer.nat. Poerbandono, ALDILA
This study discusses the problem of sedimentation with sediment budget approach. Analysis of sediments on these methods focus on the evaluation of sedimentary processes (erosion, sediment transport, and deposition of sediment particles), and shows the correlation relationship between factors such as speed of tidal currents, tides, sediment grain size, and concentration of water turbidity. Those factors that lead to sedimentation will be proven through field experiments by measuring the flow velocity, height measurements of water level, water sampling, and retrieval of bottom sediments. With the information about the current speed and the concentration of water samples, then the measurement of the amount of sediment transport rate that occurred in the study could be done. Sedimentary processes (erosion, transport, and deposition) can be determined by looking at the relationship between flow velocity and the grain size of bottom sediments.